Labour Mobility: Is the euro boosting mobility? Labour mobility in Europe during the crisis years - Jörn Quitzau; Christina Boll; Julian Sebastian Leppin (Berenberg Bank und Hamburgisches WeltWirtschaftsInstitut (HWWI), 2014)
Workers in Europe have responded to the euro crisis. Cross-border migration flows have changed considerably over recent years. However, the single currency has not yet given mobility within the eurozone a direct, visible boost. Instead, the euro crisis primarily diverted the migration flows from the new EU member states in central and eastern Europe. Instead of heading for Spain, Ireland and Italy, workers from the accession countries are now going to other countries in Europe. Some workers from central and eastern Europe have even returned to their home countries from the countries hit by the euro crisis or moved on to other European states. This redirection of the migration flows from central and eastern Europe after 2007 is playing a much greater role in labour mobility in Europe than direct internal migration from the countries badly affected by the euro crisis to economically stronger eurozone countries. Employment and incomes are the actual drivers of labour mobility in Europe. The currency is not an issue in this regard. People go where the jobs are. In addition, the persistent income gap between the countries of central and eastern Europe and western Europe is acting as a lever initiating migration. The migration balances of the crisis-hit countries have come under pressure from two sources: fast-falling immigration figures coupled with rapidly rising emigration at the same time. A number of previously popular countries for immigration, like Spain, turned into net emigration countries during the crisis. Workers are reacting to the crisis. Migrants from the new member states in central and eastern Europe have proven to be especially mobile. They head for those eurozone countries where the labour market gives them opportunities, and they leave those countries again when the situation on the labour market deteriorates badly. Migrants are increasingly young and well educated. In general, a positive selection can be observed among emigrants, measured by the distribution of education in their home countries. Highly skilled migrants are in some cases buying their job by working below their formal qualifications at the new place of work. At the same time, a job for which they are actually overqualified is the better choice for them, provided this represents the (only) alternative to unemployment in the short run. In addition, the gap between skills offered and those demanded by the labour market widened rapidly during the crisis, especially in the crisis-hit countries but also in the eurozone overall. The skill mismatch implies high structural deficits on the labour markets in the eurozone that cannot be overcome by more labour mobility alone. The rising average age of the population is likely to dampen labour mobility within Europe in the future. This makes it all the more important to address structural reforms in order to boost employment growth in Europe and the eurozone. Mobility within Europe remains a complex phenomenon, driven by a range of factors. For this reason, it is also hard to predict migration flows going forward. – – Die Arbeitskräfte in Europa haben auf die Euro-Krise reagiert. In den vergangenen Jahren haben sich die grenzüberschreitenden Wanderungsströme erheblich verändert. Allerdings hat die gemeinsame Währung Euro der Mobilität innerhalb des Währungsraumes bisher keinen direkten und sichtbaren Schub verliehen. Stattdessen hat die Euro-Krise vor allem die Wanderungsströme aus den neuen mittel- und osteuropäischen Mitgliedsstaaten der EU umgelenkt. Statt nach Spanien, Irland und Italien gehen Arbeitskräfte aus diesen Beitrittsländern jetzt in andere Länder Europas. Teilweise sind mittel- und osteuropäische Arbeitnehmer sogar aus den Euro-Krisenländern in ihre Heimatländer zurückgekehrt oder in andere europäische Staaten weitergewandert. Dieses Umlenken der Wanderungsströme aus Mittel- und Osteuropa nach 2007 spielt eine weit größere Rolle für die Mobilität der Arbeitskräfte in Europa als die direkte Binnenwanderung von den Euro-Krisenländern in wirtschaftlich stärkere Euro-Länder. Beschäftigung und Einkommen sind die eigentlichen Triebfedern der Arbeitskräftemobilität in Europa. Auf die Währung kommt es dafür nicht an. Die Menschen gehen dorthin, wo die Jobs sind. Zusätzlich wirkt das nach wie vor bestehende Einkommensgefälle zwischen den mittel- und osteuropäischen Staaten und Westeuropa als Hebel, der Wanderungen in Gang setzt. Die Wanderungsbilanzen der Krisenländer sind durch stark rückläufige Einwanderzahlen bei zugleich stark steigenden Auswanderungen doppelt unter Druck. Einige vormals beliebte Einwanderungsländer wie etwa Spanien haben sich unter der Krise zu Nettoauswanderungsländern entwickelt. Die Arbeitskräfte reagieren auf die Krise. Migranten aus den mittel- und osteuropäischen neuen Beitrittsländern erweisen sich als besonders mobil. Sie streben in diejenigen Mitgliedsländer der Währungsunion, in denen der Arbeitsmarkt ihnen Chancen bietet, und sie wandern aus ihnen wieder aus, wenn sich die Lage am Arbeitsmarkt deutlich verschlechtert. Migranten sind zunehmend jung und gut gebildet. Generell ist eine positive Selektion der Auswanderer, gemessen an der Bildungsverteilung in ihren Heimatländern, zu beobachten. Hoch qualifizierte Migranten erkaufen sich ihren Arbeitsplatz teilweise mit einem Einsatz unterhalb ihrer formalen Qualifikationen am neuen Arbeitsort. Gleichwohl ist ein Job, für den sie eigentlich überqualifiziert sind, für sie die bessere Wahl, sofern dies kurzfristig die (einzige) Alternative zur Arbeitslosigkeit darstellt. Zudem ist in der Krise die Kluft zwischen angebotenen und arbeitsmarktseitig nachgefragten Qualifikationen insbesondere in den Krisenländern, aber auch in der Eurozone insgesamt rapide angestiegen. Der Skill Mismatch weist auf hohe strukturelle Defizite an den Arbeitsmärkten in der Eurozone hin, die durch mehr Mobilität der Arbeitskräfte allein nicht zu beheben sind. Das zunehmende Durchschnittsalter der Bevölkerung dürfte die Arbeitskräftemobilität innerhalb Europas künftig eintrüben. Umso wichtiger ist es, strukturelle Reformen anzugehen, um die Beschäftigungsdynamik in Europa und dem Euroraum weiter zu steigern. Die Mobilität innerhalb Europas bleibt ein komplexes Phänomen, das von einer Vielzahl von Faktoren getrieben wird. Aus diesem Grund sind die Migrationsströme auch künftig schwer vorherzusagen.
Keywords: 330